Investigation and optimization of group III-N semiconductor thin-film growths using DC nitrogen plasma - Kadikoff, Berek (My University, 2019)
The Lakehead University remote plasma-enhanced metalorganic chemical vapour deposition (RPE-MOCVD) reactor utilizes nitrogen plasma to provide the required nitrogen species in group III-N semiconductor material growth. This plasma provides advantages over conventional MOCVD systems, typically using ammonia as the nitrogen source. An issue with using ammonia is that the dissociation temperature is high, restricting the growth of certain materials and limiting possible substrates which may be grown on. The disassociation reaction efficiency of ammonia also plateaus at a low value. With RPE-MOCVD, the system is able to perform growths at significantly lower temperatures, limited only by the metalorganic dissociation temperatures, and the nitrogen plasma species composition and production rates may be varied. In this work the nitrogen plasma used in the RPE-MOCVD reactor is investigated in order to determine how varying system settings affects plasma conditions. This is done in an effort to optimize group III-N semiconductor thin-film growth conditions in this reactor. Spectroscopic and Langmuir probe measurements are performed and analyzed as system parameters are varied to investigate the resulting plasma conditions. Experimental GaN growths are performed with varying system parameters on sapphire substrates. The resulting growths are analyzed and compared with the use of X-ray diffraction (XRD), atomic force microscopy (AFM), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX) characterization techniques.
Keywords: Thin-film growth methods; Nitrogen plasma